2015
DOI: 10.1186/s12955-015-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

A psychometric assessment of the St. George’s respiratory questionnaire in patients with COPD using rasch model analysis

Abstract: BackgroundThe St. George’s Respiratory Questionnaire (SGRQ) was a widely used tool to assess disease impact on patients with obstructive airways disease. Although traditional methods have generally supported construct validity and internal consistency reliability of SGRQ, such methods cannot facilitate the evaluation of whether items are equivalent to different individuals. The purpose of this study is to rigorously examine the psychometric properties of the SGRQ in patients with chronic obstructive pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
(63 reference statements)
2
13
0
2
Order By: Relevance
“…The main issue was the inclusion of two items in the scoring (“Sitting or lying still making feel breathless” and “Playing sports or game making feel breathless”). This finding was consistent with previous findings reported in the literature, 12 , 22 that led to the creation of the SGRQ-C. 12 The examination of cross-cultural performances of the SGRQ “Activity” items showed a great variability in the responses to these items in different global regions.…”
Section: Discussionsupporting
confidence: 91%
“…The main issue was the inclusion of two items in the scoring (“Sitting or lying still making feel breathless” and “Playing sports or game making feel breathless”). This finding was consistent with previous findings reported in the literature, 12 , 22 that led to the creation of the SGRQ-C. 12 The examination of cross-cultural performances of the SGRQ “Activity” items showed a great variability in the responses to these items in different global regions.…”
Section: Discussionsupporting
confidence: 91%
“…Kuesioner ini dapat digunakan pada pasien dengan usia 17 hingga 80 tahun dan merupakan kuesioner spesifik untuk pasien asma dan PPOK 5 . Validitas SGRQ telah dilakukan di beberapa negara terhaap berbagai penyakit pernafasan antara lain PPOK, chronic pulmonary aspergillosis dan Idiopathic Cyctic fibrosis [6][7][8] . Di Indonesia juga sudah pernah dilakukan penerjemahan dan validasi kuesioner SGRQ sebagai alat pengumpul data untuk mengukur kualitas hidup pada pasien Tuberkolosis (TB) dan hasilnya SGRQ valid dan reliabel untuk mengukur kualitas hidup pada pasien TB 9 .…”
Section: Penahuluanunclassified
“…Psychometric differences between the SGRQ domains are recognized in the literature, and it has been suggested that the SGRQ (Activity) and SGRQ (Symptoms) domains have greater accuracy [37]. In present study, depression was identified using the MINI diagnostic tool, where the influence from the patient’s subjective evaluation of their health is mitigated.…”
Section: Discussionmentioning
confidence: 93%